Effect of NSP enzyme on performance of growth and digestion for growing pigs fed paddy-based diets - XIA Mei-sheng (浙江大学学报. 农业与生命科学版)
sixty piglets (Landrace x Jia) were used to study the effects of adding NSP enzymes (including —3-glu-canase, xylanase and cellulase) to paddy-based diets on performance of growth and digestion for growing pigs. The results of experiment showed that adding NSP enzymes increased average daily gain by 8.78% (P<0.05), decreased feed gain ratio by 9.42% (P<0.05) compared with the control group. The apparent digestibilities of CP, EE and CF were elevated by 18.76% (P<0.01)、16.04% (P<0.05)、108.57% (P<0.05) respectively. Incidence of diarrhoea, numbers of E. Coli in faeces, viscosity in the supernatant of the duodenal, jejunal and digesta were reduced by 37.00% (P<0.05), 81.29% (P<0.05), 2.8% (P>0.05), 7.08% (P<0.01) and 6.78% (P<0.01), respectively. Activities of total proteolytic enzyme and α-amylase in duodenal content were promoted by 99.07% (P<0.01) and 18.41% (P<0.05) respectively compared to control group.